FRI0229 The validity of the omeract ultrasound definitions of gout elementary lesions in the diagnosis of gout. (12th June 2018) - Christiansen, S.N.; Østergaard, M.; Slot, O.; Terslev, L.
Abstract : Objectives: The aim was to evaluate ultrasound (US) as a diagnostic tool for gout using the OMERACT US Working Group's 2015 US definitions for elementary lesions in gout using a) positive urate crystal microscopy or b) clinical diagnosis of gout blinded to the US assessment as gold standard for determining the sensitivity and specificity of each elementary lesion. Methods: US examination (28 joints, 26 tendons) were performed in patients with clinically suspected gout. Joints were evaluated for the four OMERACT elementary lesions of gout (Double contour (DC), Tophus, Aggregates and Erosions) and tendons for aggregates and tophus. The lesions were registered as either present or absent for each patient. The US assessment was compared to 2 different gold standard references: 1) presence/absence of monosodium-urate (MSU) crystals by joint fluid microscopy and 2) the final clinical diagnosis based on the clinical assessment by a rheumatologist, blinded to US findings but not microscopy findings (table 1). Results: 51 patients (44 males, 7 female), mean age of 62(30 – 89) years were included. 34 of these had a positive microscopy for MSU crystals whereas 15 patients had a negative microscopy and in 2 patients joint aspiration was not possible. Of the patients without positive microscopy 3 were clinically diagnosed as having gout by a US blinded assessor whereas 14 were diagnosed with other diseases. DC, tophus and aggregates were found to be statistically significantly more frequent in both patients with positive MSU microscopy and in patients with clinically diagnosed gout (p-values range from 0.003 to <0.0001), compared to patients with negative MSU microscopy and other clinical diagnoses, respectively. All four elementary lesions were found to have high sensitivity (ranges from 0.74–0.88) for gout, both when MSU microscopy and when clinical diagnosis was used as gold standard reference. DC and aggregates had the highest sensitivities (0.85–0.88). Low specificity (0.33–0.64) was found for both aggregates and erosions, both when microscopy and clinical diagnosis was considered the gold standard. In contrast, DC and tophus showed high specificities for patients with microscopically proven gout (0.73 and 0.87, respectively) and particularly patients with clinically diagnosed gout (both 0.93). DC and tophi were also found to have high positive predictive values (PPV) for gout for patients with microscopically proven gout (0.88 and 0.93, respectively) and especially for patients with clinically diagnosed gout (both 0.97). In contrast negative predictive values (NPV) were relatively low for all lesions (ranges from 0.36–0.72). Conclusions: The OMERACT US definitions of gout elementary lesions seem to be a valid tool for diagnosis of gout in clinical practice. Particularly, DC and tophi seem to have a high specificity and high PPV for the disease. Disclosure of Interest: None declared